2011
DOI: 10.1586/erd.11.4
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic rotator cuff repair: suture anchor properties, modes of failure and technical considerations

Abstract: Rotator cuff injury and tears are a common source of shoulder pain, particularly among the elderly. Arthroscopic repair has now become the mainstay in the treatment of significant injuries that have failed conservative therapy. Compared with the traditional open technique, arthroscopic repair offers patients smaller incisions and less soft-tissue trauma, which result in improved postoperative pain and rehabilitation. The advances that have made arthroscopic repairs a reality includes improvement in arthroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 53 publications
0
29
0
1
Order By: Relevance
“…15) Failure at the anchor-bone interface is not uncommon, and some recent clinical studies have assessed the suitability of this interface with respect to bone quality. [1][2][3][4][5] BMD has been proposed as a good predictor of the mechanical integrity of trabecular bone. 16) However, global measures of bone quality can only explain implant stability to a limited extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15) Failure at the anchor-bone interface is not uncommon, and some recent clinical studies have assessed the suitability of this interface with respect to bone quality. [1][2][3][4][5] BMD has been proposed as a good predictor of the mechanical integrity of trabecular bone. 16) However, global measures of bone quality can only explain implant stability to a limited extent.…”
Section: Discussionmentioning
confidence: 99%
“…Failure could occur at the anchor-bone interface, the tendon suture interface, the anchor-suture interface, or the suture itself. [1][2][3][4][5] In addition, poor bone quality caused by osteoporosis has been suggested to play a role in suture anchor failure at the anchorbone interface after rotator cuff repair. [6][7][8] Bone quality is usually evaluated by dual energy X-ray absorptiometry (DXA), which is regarded as the gold standard for determining global bone mineral density (BMD); however, it does not correlate with the proximal humerus BMD.…”
Section: Introductionmentioning
confidence: 99%
“…Anchors pulled out of cancellous bone 18% of the time at an average of 4300 cycles of the 10 -180 N load which is significantly greater than a RCR would be subjected to during the healing phase. A previous study of RCRs concluded that condition of the tissue or bone was the limiting reason for repair failure [15][16][17]. High UFLs and the high number of cycles before pullout of generic anchors from cancellous bone indicate the anchors will not be the limiting factor of RCRs.…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder arthroscopy is a relatively safe and minimally invasive orthopedic procedure, offering good functional results [1]. It has grown in popularity over the past decades specially basing on these highly praised advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic revision of rotator cuff lesions is an increasingly popular procedure nowadays due to the convenience of its minimally invasive nature, associated with a relatively safe profile [1, 2]. One of the most feared complications of shoulder arthroscopy, although rare, remains deep articular infection, with potentially destructive joint sequelae [24].…”
Section: Introductionmentioning
confidence: 99%